Terminology of Roman Criminal Law – crimen et delictum - Miroslav Frýdek (Journal on European History of Law, 2024)
This study explores the dualistic nature of Roman criminal law, highlighting the distinction between private law (ius privatum) and public law (ius publicum). It focuses on the key terms "crimen" and "delictum" and their significance in categorizing acts as breaches of private or public legal duties. The study also examines the prosecution of crimes, the role of popular actions, and the different sanctions imposed. By analyzing these concepts, the study sheds light on the foundational principles and classifications within Roman criminal law.